2020
DOI: 10.3897/herpetozoa.33.e47293
|View full text |Cite
|
Sign up to set email alerts
|

Variation in species richness, composition and herpetological community structure across a tropical habitat gradient of Palawan Island, Philippines

Abstract: Information on species richness and community structure is invaluable for guiding conservation and management of biodiversity, but is rarely available in the megadiverse biodiversity conservation hotspot of Philippines – particularly for amphibians and reptiles. This study provides the first report and characterisation of amphibians and reptile communities across primary habitat types of the Victoria-Anepahan Mountain Range on Palawan Island along the western edge of the archipelago. A total of 41 amphibian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 68 publications
(85 reference statements)
2
14
0
Order By: Relevance
“…38). Previous studies have observed this same pattern: generally, the archipelago's richest herpetofauna diversity estimates have been recorded in lower montane forests, including moderate percentages of Philippine-endemic species, with species diversity varying inversely-proportional to elevation (however, higher proportions of Philippine-endemic species result from wellstudied sites at higher elevations; Brown et al 2000;Siler et al 2012;Supsup et al 2020).…”
Section: Discussionmentioning
confidence: 60%
“…38). Previous studies have observed this same pattern: generally, the archipelago's richest herpetofauna diversity estimates have been recorded in lower montane forests, including moderate percentages of Philippine-endemic species, with species diversity varying inversely-proportional to elevation (however, higher proportions of Philippine-endemic species result from wellstudied sites at higher elevations; Brown et al 2000;Siler et al 2012;Supsup et al 2020).…”
Section: Discussionmentioning
confidence: 60%
“…Concerning pattern (i), there is wide available literature showing that lizard communities are signi cantly more species-rich in tropical forests than in more open or degraded environments (Lewin et al 2016), the same as generally observed in both vertebrates and invertebrates (e.g., Basset et al 2008;Watling and Donnelly 2008). For instance, in the Philippines Supsup et al (2020) found that higher species richness was found in secondary forests than in mixed-use agricultural areas. Since habitat heterogeneity is an important predictor in explaining lizard richness in Africa (Lewin et al 2016), it is likely that the multiple microniches available in the hilly forests of the Togo hills may explain the much higher species richness that we observed therein in comparison with savannah and suburban habitats of the same study region.…”
Section: Discussionmentioning
confidence: 71%
“…Most studies on community structure along tropical habitat gradients have focused so far on habitats that have been modi ed by humans during recent times, for instance burnt versus non-burnt areas (Akani et al 2018;Costa et al 2020) or forest-plantation mosaics (Palmeirim et al 2017;Supsup et al 2020). However, almost no investigation has been carried out on community structure of any vertebrate groups along habitat gradients that were modi ed by humans in historical or prehistorical times, despite these studies may be important for a better under standing of the community dynamics along habitat gradients.…”
Section: Introductionmentioning
confidence: 99%
“…We surveyed 5 transects into each of two habitats (mixed agricultural areas and mature secondary growth forests). Transects were 100 m long by 10 m wide (Heyer et al 1994;Diesmos 2008;Supsup et al 2016), marked with luminous ribbon strips placed 10 m apart. We employed visual encounters, opportunistic catching, and microhabitat searches (e.g., limestone crevices, tree trunks, and decaying logs), during daytime (07:30-11:30 h) and night time (18:30-23:30 h).…”
Section: Methodsmentioning
confidence: 99%
“…Mostly nocturnal, they feed on insects and small arthropods and play a vital role in pest control (Newbery and Jones 2007;Tkaczenko et al 2014;Meiri 2019). They inhabit a range of environments from builtup areas, mixed agricultural plantations, and lowland forests (Siler et al 2012;Sanguila et al 2016;Supsup et al 2016Supsup et al , 2020.…”
Section: Introductionmentioning
confidence: 99%